Determinants of pre-menarcheal knowledge of menstruation and sociocultural implications in college going girls: A community-based cross-sectional study from Latur, Maharashtra - Namrata Arvind Thakur; Vimal Madhavrao Holambe (Wolters Kluwer Medknow Publications, 2016)
Introduction: Adolescence marks the onset of female puberty. The first menstruation is often horrifying and traumatic to an adolescent girl because it usually occurs without her knowing about it. Implications of a girl's response to menarche have a socio-cultural and religious significance. Aim and Objective: To study the sociocultural and physiological implications of menstruation in college going girls. Materials and Methods: This was a community-based cross-sectional observational study undertaken among college girls. All the girls (n = 252) of the college were enrolled in the study. A structured questionnaire was used as the study tool. The questionnaire included topics related to sociodemographic information, sociocultural implications and first informant about the physiological process of menstruation along with its timing. Results: Majority of the study subjects (77.40%) observed restrictions for religious/holy things. Sleep disturbances were the most common (59%) disturbance faced by the study subjects. Of a total of 252 respondents, majority [104 (41.30%)] had leg cramps. The first informant of menstruation was the mother in 196 (77.78%) girls. Of 252 girls, 86 (34.12%) had pre-menarcheal knowledge of menstruation. Mothers from the urban area and with better education tend to give knowledge of menstruation prior to menarche of her daughter. An increasing trend was observed with increasing educational status of the mother and proportion of them giving pre-menarcheal knowledge of menstruation to their daughter. Conclusions: Menstruation is associated with a high burden of sociocultural implications. Pre-menarcheal knowledge of menstruation is poor. Mothers from the urban area and with better educational level tend to give knowledge of menstruation prior to menarche of their daughter.